Immediate Action - McNab, Andy, 1959- (London Bantam Press, 1995)
The author shares his life from when he was found on the steps of Guy's Hospital to when he went to fight in the Gulf War. He grew from a delinquent youth to a young soldier fighting the IRA in Northern Ireland. As a member of an SAS Regiment he was involved in covert operations for nine years, on five continents
Include Color Illustration and Glossary
Keywords: Soldiers -- Great Britain -- McNab, Andy, 1959-